2017
DOI: 10.1186/s12977-017-0363-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of chromatin structure by the FACT histone chaperone complex regulates HIV-1 integration

Abstract: BackgroundInsertion of retroviral genome DNA occurs in the chromatin of the host cell. This step is modulated by chromatin structure as nucleosomes compaction was shown to prevent HIV-1 integration and chromatin remodeling has been reported to affect integration efficiency. LEDGF/p75-mediated targeting of the integration complex toward RNA polymerase II (polII) transcribed regions ensures optimal access to dynamic regions that are suitable for integration. Consequently, we have investigated the involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 56 publications
4
40
1
1
Order By: Relevance
“…CBL0137 blocked viral replication to the same extent as CBL0100 without any cytotoxicity (Figure S2). However, these results contrast with Matysiak et al's paper, which showed that CBL0137 targeting of the FACT complex facilitated HIV‐1 integration by 1.5‐fold and enhanced early steps of HIV‐1 replication. Nevertheless, the emphasis was strictly put on studying FACT at the integration step and these experiments were limited to HeLa or HEK293 cells, which do not recapitulate the cellular tropism of HIV‐1.…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…CBL0137 blocked viral replication to the same extent as CBL0100 without any cytotoxicity (Figure S2). However, these results contrast with Matysiak et al's paper, which showed that CBL0137 targeting of the FACT complex facilitated HIV‐1 integration by 1.5‐fold and enhanced early steps of HIV‐1 replication. Nevertheless, the emphasis was strictly put on studying FACT at the integration step and these experiments were limited to HeLa or HEK293 cells, which do not recapitulate the cellular tropism of HIV‐1.…”
Section: Resultscontrasting
confidence: 91%
“…Using Spina et al's article on the evaluation of antilatency drugs (where the viability of compounds ranged from 69% to 96%), a concentration of CBL0137 maintaining cell death less than or equal to 10% (CC 10 ) across all cell lines was selected 0.5 µM (Table S2). Interestingly, this concentration was also used by another group for CBL0137 in a report investigating the importance of FACT complex in HIV‐1 integration …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…La région C-terminale de la protéine NUP153, contenant 29 motifs FG, est responsable de l'interaction avec la capside du VIH-1 [6]. De [10]. Si le facteur LEDGF/p75 permet une intégration dans des zones précises du génome de l'hôte, il a été montré que ce n'est pas la seule protéine à faciliter l'amarrage des complexes viraux à la chromatine : il semble que d'autres facteurs participent également à cette fonction.…”
Section: Nouvelleunclassified